1976
DOI: 10.1039/c3976000052a
|View full text |Cite
|
Sign up to set email alerts
|

Generation and reactivity of aminyl and aminylium radicals

Abstract: Photolysis of N-nitropiperidine under neutral conditions generates the piperidinyl radical and under acidic conditions the piperidinylium radical, indicated by their addition reaction with cyclohexene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A number of intramolecular photoreductions of ketoamines are characterized by their insensitivities to triplet quenchers (e.g., dienes) and low quantum yields as opposed to high product yields. The nature of these reactions strongly supports the intermediacy of a fast Intramolecular charge-transfer interaction process (eq 76-78).299-301 -Ar2C-0-CHR'NR2 (72) pounds (eq 70 and 71) or coupling with the intermediate radicals (eq 72). 288 The overall reaction is the oxidation of amines to alkylidenimines balanced by reduction of carbonyl compounds to plnacols (or hydrols).…”
Section: G Other Reactionsmentioning
confidence: 77%
“…A number of intramolecular photoreductions of ketoamines are characterized by their insensitivities to triplet quenchers (e.g., dienes) and low quantum yields as opposed to high product yields. The nature of these reactions strongly supports the intermediacy of a fast Intramolecular charge-transfer interaction process (eq 76-78).299-301 -Ar2C-0-CHR'NR2 (72) pounds (eq 70 and 71) or coupling with the intermediate radicals (eq 72). 288 The overall reaction is the oxidation of amines to alkylidenimines balanced by reduction of carbonyl compounds to plnacols (or hydrols).…”
Section: G Other Reactionsmentioning
confidence: 77%
“…It was already demonstrated that one equivalent of NADPH was required to effect anaerobic denitration of one molecule of RDX by the XplB-XplA system (5), but the exact mechanism of electron transfer in the case of XplA remains to be elucidated. Single electron transfer mechanisms have also been established for cyt-P450 acting on a number of substrates (36) and implicated in the abiotic photolytic denitration of, for example, N-nitro-piperidine (37). Given a possible oxygen-independent electron transfer hypothesis as a basis for denitration of RDX, it would not be necessary to consider the structural determinants of a mechanism, which would include, for example, base-catalyzed elimination of HNO 2 , which is known to occur for nitramines under basic conditions (38); nor is it necessary to consider the positioning of the RDX ligand for C-H hydroxylation, because the denitration is known to be catalyzed in an anaerobic environment.…”
Section: Structure Of Xpla-hemementioning
confidence: 99%
“…Both photolyses of TMT under neutral conditions and TMT-H+ under acidic conditions are not quenched by oxygen, which finds similarity in photolysis of TV-nitroso-29 and TVnitroamines. 25 This suggests that the dissociations of photoexcited TMT or TMT-H+ are very fast and probably faster than bimolecular collisions with oxygen molecules in the solution. All of these photolyses are excellent methods to generate aminium radicals and good synthetic methods for /3-amino alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…By a peak matching technique, the 37min peak was identified as the trans alcohol 10 and the 12-min peak as 9. 9 was separated by preparative VPC as an oil: IR 3020, 2828, 2779 (s), 1688 (w), 1458 (s), 1264, 1177, 1154, 1043, 1032, 994, and 727 (s) cm-1; mass spectrum m.e (rel intensity) 153 (M+, 25), 138…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation